DIFFERENCES BETWEEN THE PATHOGENICITY OF Edwardsiella tarda AND Aeromonas hydrophila THROUGH FEED ON THE SURVIVAL RATE OF AFRICAN CATFISH ( Clarias gariepinus ) FRY - Kusnadi, Kusnadi; Nainggolan, Armen; Lestira, Yudha (Advances in Social Sciences Research Journal, 2019)
ABSTRACT African catfish (Clarias gariepinus) is an important commodity in freshwater fish cultivation and is popular in Indonesia. The bacteria Aeromonas hydrophila and Edwardsiella tarda are bacteria that are dangerous to freshwater cultivation. This study aimed to discover the difference in the pathogenicity of Aeromonas hydrophila and Edwardsiella tarda through feed on the survival of African catfish fry. The study employed a Completely Randomized Design with 3 treatments and 3 replications: treatment A (exposed to Edwardsiella tarda through feed), B (exposed to Aeromonas hydrophila through feed), and K/control (administration of feed without bacteria). The feed was administered ad libitum, the observation was conducted for 25 days, and the fish were kept in 9 aquariums at a seeding density of 100 individuals/aquarium (32L capacity). The observation parameters consisted of clinical signs, mortality, body weight increase, feed consumption rate, histopathological assessments, and water quality measurements. The results of the study revealed that Aeromonas hydrophila had a more significant effect on the survival rate of African catfish fry compared to Edwardsiella tarda (treatment A). The highest mortality in the test fish was demonstrated by treatment B (feed with Aeromonas hydrophila, 88% mortality). Treatment A (feed with Edwardsiella tarda) had a mortality rate of 68% and treatment K (without the addition of bacteria) had a mortality rate of 11%. Keywords: African catfish (Clarias gariepinus), Aeromonas hydrophila, Edwardsiella tarda, pathogenicity